PENGARUH PROJECT BASED LEARNING TERHADAP MOTIVASI BELAJAR, KREATIVITAS, KEMAMPUAN BERPIKIR KRITIS, DAN KEMAMPUAN KOGNITIF SISWA PADA PEMBELAJARAN BIOLOGI - Insyasiska, Dewi; Zubaidah, Siti; Susilo, Herawati (Universitas Negeri Malang, 2015)
This research aims to determine the effect of Project Based Learning to increase student’s motivation, creativity, critical thinking and cognitive abilities in learning biology. This quasi-experimental research design was